Roles of macrophages on ulcerative colitis and colitis-associated colorectal cancer - Maorun Zhang; Xiaoping Li; Qi Zhang; Jiahua Yang; Gang Liu (Frontiers in Immunology, 2023)
Colitis-associated colorectal cancer is the most serious complication of ulcerative colitis. Long-term chronic inflammation increases the incidence of CAC in UC patients. Compared with sporadic colorectal cancer, CAC means multiple lesions, worse pathological type and worse prognosis. Macrophage is a kind of innate immune cell, which play an important role both in inflammatory response and tumor immunity. Macrophages are polarized into two phenotypes under different conditions: M1 and M2. In UC, enhanced macrophage infiltration produces a large number of inflammatory cytokines, which promote tumorigenesis of UC. M1 polarization has an anti-tumor effect after CAC formation, whereas M2 polarization promotes tumor growth. M2 polarization plays a tumor-promoting role. Some drugs have been shown to that prevent and treat CAC effectively by targeting macrophages.